Selected Factors Students’ Stress in Learning English: A Case Study of English Study Program - Rahmadani Putri; Mayang Sastra Sumardi; Muhammad Ikrar Nugraha (Universitas Muhammadiyah Enrekang, 2022)
The purposes of this research are to find out kinds of stresses suffered by the students in learning English and to investigate the factors related to students’ stresses in learning English. This research focused on getting the data about selected factors students’ stress in learning English. The researcher chose 8 students who come from 4 bachelor’s degree students, and 4 master’s degree students as the participants of this research. For the 4 bachelor’s degree students, the students were those who were in the 1st semester and got GPA at least B+ (75-76) on the English study program. Then, for the 4 master’s degree students, the students were also those from the 1st semester and got GPA at least B+ (75-76) and the English study program. All the data of this research were collected through open-ended questionnaires and interviews. The results of this research show that the stressed feeling suffered by the students in learning English is such a negative stress since there is not any positive response, and it categorized as stress in the society, and followed by stressed within the person. Then, the researcher found mostly they feel stressed in learning English because of afraid of making mistake in learning English, if they make mistake while learning English in the class, there will be something happened such as the friends will mock at them or underrate them, and so do the lecturer.